INFLUENCE OF DIETARY PHYTIC ACID AND PHYTASE ON GROWTH, DIGESTIBILITY, AND VERTEBRAL PHOSPHORUS OF JUVENILE JAPANESE FLOUNDER, Paralichthys olivaceus - Asda Laining (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Triplicate groups of juvenile Japanese flounder (0.56 g) were fed with six experimental diets to examine the effects of phytic acid, with or without phytase on growth performances, nutrient digestibility, and vertebral phosphorus (P) content. Diet without both phytic acid (PA) and phytase supplementation was used as control. One diet was added with 10 g PA/kg without phytase supplement. Four diets were formulated to contain two levels of phytase (1,000 FTU or 2,000 FTU phytase/kg diet) combined with 2 levels of PA (10 and 20 g/kg diet). All diets were added with 10 g/kg in-organic P to meet flounder requirement. After 50 days culture, fish fed 10PA/2,000P grew significantly (P<0.05) higher than other groups, but did not differ from fish fed 10PA/1,000P. In contrast, fish fed 10PA/0P had the lowest growth but was not different from control diet (0PA/0P). Addition of either PA or combined with phytase had no significant (P>0.05) effects on feed intake and FCR. However, fish fed 10 g PA/kg combined with phytase had significant (P<0.05) higher whole body lipid, ash, and P than other groups. Moreover, P digestibility and vertebral P content were significantly increased by dietary phytase. This finding suggested that dietary phytase had potential to enhance the growth and nutrient utilization in juvenile Japanese flounder fed diet containing phytic acid. Specifically, inclusion of 2,000 FTU phytase/kg diet gave better performances when diet containing PA at level of 10 g/kg diet.